The coupling of thermal and athermal effect in high-density multiple pulse continuous treatment of AZ31. (March 2022) - Wang, Ruijuan; Xu, Zhuohui; Jiang, Yanbin; Tang, Guoyi; Wan, Junxi; Chou (Zhou), Kevin Jenn-Chien (Zhenqian); Li, Qiulin
Graphical abstract: Highlights: High-density multiple pulse treatment is a process of rapid temperature change. The linear model of the maximum stable temperature (Tm ) of strip surface was put forward through theoretical calculation. The promotion of athermal effect produced during HMPT on the dislocation climbing speed can stimulate, only with sufficient thermal effect. Abstract: Electropulsing process of magnesium alloy has attracted a substantial attention, owing to the advantage of the low consumption, high efficiency and short processing period. High-density multiple pulse treatment (HMPT) in the paper can be applied into the industry, due to the continuous process. Therefore, the evolution information of AZ 31 strips treated by HMPT, such as the surface temperature, the microhardness and the microstructure was observed. It was indicated that HMPT belonged to the process of the rapid temperature change. The thermal effect produced by high-density multiple pulse was investigated. On the basis, the linear model of maximum stable surface temperature of AZ 31 was deduced in theory and consistent with the experimental data; and its influence on the recrystallization nucleation in HMPT were investigated. Compared with the conventional heat treatment, the recrystallization temperature decreased from 483 K to 465 K (maximum surface temperature) during HMTP, as well as the recrystallization time was shortened by 10 2, resulting from the significant increase of dislocation climbing speed. The complex coupling between thermal effect and athermal effect made dislocation climbing motion remarkable increase through quantitative calculation and qualitative analysis, and the remarkable growth of dislocation climbing speed was calculated about 10 4 during HMPT.